Investigating relationship between corporate social responsibility and corporate financial performance: the case of Chinese listed companies - Zhang, Jinyu (2020)
As an important part of the market economy, listed enterprises actively perform their corporate social responsibilities (CSR) has attracted the attention of the whole society. The increasing severity of social and environmental issues has prompted consumers to pay attention to whether companies fulfill their CSR. The fulfillment of environmental, social, employee, and community responsibilities is conducive to the listed company's establishment of a good social image. The main research object of this study is the relationship between CSR and corporate financial performance (CFP) of listed enterprises in China. The research subject is China's A-share listed enterprises and financial data. And this research also studies the impact of CSR on corporate financial performance under different company nature and ownership concentration. This research verifies the three hypotheses proposed in this study. Through empirical research, this study draws the following conclusions: Chinese listed companies' CSR is significantly positively correlated with corporate financial performance. Compared with non-state-owned enterprises, the increase in CSR of SOE enterprises has improved ROA more significantly. Compared with listed companies with high ownership concentration, the increase in CSR of Chinese listed companies with low ownership concentration can significantly increase ROA.